Universal daycare and mothers' working lifetime - Sarah Sander (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
This paper examines the effects of universal daycare on mothers' labor force participation, full-time employment, and earnings over their working lifetime. I exploit differential access to daycare caused by a roll-out of daycare centers across Denmark in combination with rich administrative data. Daycare availability has persistent effects on labor force participation and increases long-run earnings. Reduced fertility and parental separation are potential mediators behind the participation effects. For higher-educated mothers, participation effects diminish over time, whereas earnings effects prevail in the long run. These results suggest that labor market attachment during child-rearing years has important long-run economic consequences.
Keywords: J13; J22; 330; child care; female labor supply